Pengaruh kemahiran penyeliaan pengurusan sekolah, sikap guru terhadap kemahiran penyeliaan dan kompetensi pengajaran guru Sekolah Menengah Kebangsaan di Negeri Kedah - Puteri Darishah, Dali (2018)
Teaching competence of teachers is the most important factor to excellence and organizational development of the school. However, the Inspectorate of Quality Assurance report found teaching competency of teachers in Malaysia are in the medium level. Past studies conducted on the supervision of teaching in schools mainly focus on the principal as a main contributor without taking into account the importance of the role of the school management, especially senior assistant, senior teacher and chairman of the committee, who also responsible for developing the school. This study aims to identify the supervision skill of teaching by school management, attitude towards supervision skills and teaching competency of teachers. The sample consisted of 316 teachers in the district of Kubang Pasu, Kedah. Three questionnaires were used, namely the supervision skills of teaching by Ebmeier, attitude towards skill supervision by Ramin, Mohammad, and Kaivan and teaching competency of teachers by Coker, Medley and Soar. Data were analyzed using Statistical Package for Social Science SPSS 22.0 and Modeling Partial Least Squares (PLS-SEM 3.0). This study found that implementation of the supervision skills of teaching has a significant relationship with teachers' attitudes toward supervision skills and teaching competence. Nevertheless element interpersonal skills found to be not significantly related to the competence of teaching, otherwise element of knowledge and technical skills has a significant relationship to the competence of the teacher. This study also found that teachers’ attitude towards supervisory skills exerted indirect effect that is the mediating effect between the supervisory skills of school management and teachers’ teaching competence. In this regard, this study will provide positive implications if the school management intends to improve teaching competence among teachers. Thus, the emphasis should be stress on the positive attitude of the teachers towards supervisory skills. The findings of this study have also contributed to the development of methods of supervision of the implementation of the supervision skills, attitude towards supervision skills and teaching competency of teachers in schools.